Sunni-Shiah Conflict Post Arabic Spring: Searching The Political Motives Behind The War on Sustainable War in Syria - Rachik Samer (International Journal of Science and Society, 2020)
The Syrian War is one of a long-standing conflict that has lasted for eight years. The difficulty of finding a peaceful spot is the cause of the conflict eradication efforts in the country. This study aims to explore the motives behind the war in Syria using the Historical approach. The results of the study and analysis found that Syria as a secular state, separating between state and religious life, besides that Syria is also a peaceful ethnoreligious state before the war-damaged the joints of life there. Bashar al Assad as Syrian president embraced the Shia teachings of the Awali sect which is a minority sect in Syria, his appointment as well as his father were supported by most of the military figures who were Sunni schools. The above explanation clearly shows that the differences in schools between Sunnis and Shiites in Syria are not the main cause of a long war. Deeper, the results of the analysis show that there are various conflicting groups in the country, namely the Syrian Government, the Syrian Democratic Forces (Rojava, SDF, QFD), the Islamic State of Iraq and Sham (ISIS), Jabhat al-Nusra, and the Syrian Opposition. Difficult resolution of conflicts that occur is not only caused by the many internal warring groups that have their own goals and interests, but this is also made worse by the involvement of other countries such as Russia, Saudi Arabia, Iran, Israel, Turkey, America, Britain and France that carry a variety of motives and interests, this is what makes it difficult to create a consensus that leads to peace in Syria.